1995
DOI: 10.1109/71.406955
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the verification of cache coherence protocols

Abstract: In this paper, we introduce a cache protocol verification technique based on a symbolic state expansion procedure. A global FSM (Finite State Machine) model characterizing the protocol behavior is built and protocol verification becomes equivalent to finding whether or not the global FSM may enter erroneous states. In order to reduce the complexity of the state expansion process, all the caches in the same state are grouped into an equivalence class and the number of caches in the class is symbolically represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(1 citation statement)
references
References 22 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…While several static techniques have been developed to prove that a sharedmemory implementation (or cache coherence protocol) satisfies SC [1,4,[9][10][11][12]17,20,23,27,28] few have addressed dynamic techniques such as testing and runtime verification (which scale to more realistic implementations). From the complexity standpoint, Gibbons and Korach [21] showed that checking whether a history is SC is np-hard while Alur et al [4] showed that checking SC for finite-state shared-memory implementations (over a bounded number of threads, variables, and values) is undecidable [4].…”
Section: Related Workmentioning
confidence: 99%
“…While several static techniques have been developed to prove that a sharedmemory implementation (or cache coherence protocol) satisfies SC [1,4,[9][10][11][12]17,20,23,27,28] few have addressed dynamic techniques such as testing and runtime verification (which scale to more realistic implementations). From the complexity standpoint, Gibbons and Korach [21] showed that checking whether a history is SC is np-hard while Alur et al [4] showed that checking SC for finite-state shared-memory implementations (over a bounded number of threads, variables, and values) is undecidable [4].…”
Section: Related Workmentioning
confidence: 99%